Green diastereospecific synthesis of various medicine analogues containing dipeptides and release of the medicines by Baker's yeast. (19th November 2022) - Jung, Sunghee; Satoh, Shin; Daitoku, Hideyuki; Noguchi, Takuya; Kawashima, Yuya; Imai, Nobuyuki
Abstract: We have succeeded green and economical synthesis of various dipeptides in 76–99% yields with 70–>99% de and dipeptides-containing medicine analogues in 74–99% yields with 79–97% de in aqueous THF at −15 °C via the mixed carbonic carboxylic anhydrides by the activation of the corresponding carboxylic acids. We observed that the anilide l -Phe-l -Phe-NHC6 H4 -4-OH, one of the deprotecting medicine analogues, was cleaved at the C -terminal of l -phenylalanine (l -Phe) by Baker's yeast under starvation conditions followed by treatment of a freshly prepared PhCH2 CH2 CO2 CO2 Et from 3-phenylpropanoic acid, ClCO2 Et, and Et3 N in MeCN to afford PhCH2 CH2 CONHC6 H4 -4-OH and PhCH2 CH2 CO-l -Phe-NHC6 H4 -4-OH in 46% and 42% yields, respectively. Interestingly, biocatalytic hydrolysis of l -Phe-d -Phe-NHC6 H4 -4-OH by Baker's yeast gave PhCH2 CH2 CO-d -Phe-NHC6 H4 -4-OH in 20% yield and PhCH2 CH2 CO-l -Phe-d -Phe-NHC6 H4 -4-OH 60% recovery yield. Graphical abstract: Image 1